Reaching Across the Waters : Facing the Risks of Cooperation in International Waters - Subramanian, Ashok; Brown, Bridget; Wolf, Aaron (Washington, DC: World Bank, 2013)
This study reviews the experience of cooperation in selected international river basins and during selected time periods in those basins. The review is from a country perspective and focuses on the countries' perceived risks and opportunities in engaging in regional cooperation deals in response to the prospects for cooperation. It is primarily aimed at external development partners who promote regional public goods (river basin institutions and agreements) and support cooperative activities and investments in international waters. We also believe that countries and individuals engaged in international waters issues will find this study and reflections helpful in enhancing their knowledge and advancing their actions with respect to regional cooperation. The specific purpose of the study is to alert teams engaged in promoting cooperation in international waters to the need for a careful risk analysis and for the formulation of a risk reduction strategy to help countries move toward cooperation.